Turbulence elasticity: a key concept to a unified paradigm of L → I → H transition. (30th March 2015) - Guo, Z.B.; Diamond, P.H.; Kosuga, Y.; Gürcan, Ö.D.
Abstract: We present a theory of turbulence elasticity, which follows from delayed response of drift waves (DWs) to zonal flow (ZF) shears. It is shown that when |〈 V 〉′ZF |/Δ ω k ⩾ 1, with |〈 V 〉′ZF | the ZF shearing rate and Δ ω k the local turbulence decorrelation rate, the ZF evolution equation is converted from a diffusion equation to a telegraph equation. This insight provides a natural framework for understanding temporally periodic ZF structures, e.g., propagation of the ZF/turbulence intensity fronts. Furthermore, by incorporating the elastic property of the DW–ZF turbulence, we propose a unified paradigm of low-confinement-mode to intermediate-confinement-mode to high-confinement-mode (L → I → H ) transitions. In particular, we predict the onset and termination conditions of the limit cycle oscillations, i.e. the I-mode. The transition from an unstable L-mode to I-mode is predicted to occur when Δ ω k < |〈 V 〉′ZF |<〈 V 〉′cr, where 〈 V 〉′cr is a critical flow shearing rate and is derived explicitly. If |〈 V 〉′ E × B | > 〈 V 〉′cr (〈 V 〉 E × B is mean E × B shear flow driven by edge radial electrostatic field), the I-mode will terminate and spiral into the H-mode.